PENGUATAN PENGETAHUAN DETEKSI DINI KANKER PAYUDARA MELALUI GERAKAN SADARI PADA SISWI KELAS 3 SMPN 2 KERAMBITAN - Evvy Anjar Puspitasari; Ika Sumiyarsi Sukamto (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service aimed to assess the effectiveness of SADARI education in increasing knowledge of early breast cancer detection among 9th-grade female students at SMP Negeri 2 Kerambitan. The activity used a quasi-experimental approach with a one-group pre-test and post-test design involving 76 participants. Educational interventions were conducted through interactive lectures and live demonstrations explaining the concept, purpose, procedure, and benefits of SADARI. The results showed a significant improvement in students’ knowledge after the intervention. Before education, 82.43% had good knowledge, increasing to 94.59% afterward. This indicates that SADARI education effectively enhances students’ understanding and awareness of breast cancer prevention. It is recommended that schools routinely integrate SADARI education into adolescent reproductive health programs.